2017
DOI: 10.1093/ofid/ofx087
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Northeastern African Rift Valley Fever Virus Lineage During the 2015 Outbreak in Mauritania

Abstract: Background.Rift Valley fever (RVF) is an acute viral anthropozoonosis that causes epizootics and epidemics among livestock population and humans. Multiple emergences and reemergences of the virus have occurred in Mauritania over the last decade. This article describes the outbreak that occurred in 2015 in Mauritania and reports the results of serological and molecular investigations of blood samples collected from suspected RVF patients.Methods.An RVF outbreak was reported from 14 September to 26 November 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…Since its first recognition in 1931 in Kenya, RVF outbreaks have been regularly reported in sub-Saharan Africa [10][11][12][13][14][15][16], the Indian Ocean [17,18] and the Arabian Peninsula [19]. The most recent outbreaks occurred in Mauritania (2015), Niger (2016), Uganda (2016) and Mayotte (2018-2019) [10,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Since its first recognition in 1931 in Kenya, RVF outbreaks have been regularly reported in sub-Saharan Africa [10][11][12][13][14][15][16], the Indian Ocean [17,18] and the Arabian Peninsula [19]. The most recent outbreaks occurred in Mauritania (2015), Niger (2016), Uganda (2016) and Mayotte (2018-2019) [10,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Backup serological diagnostics at IPD used in-house IgM/IgG ELISA assays for RVFV, DENV, and YFV. It also provided partial sequencing of DENV E- [ 31 ], NS5- [ 32 ], and NS5/3-NCR [ 33 ] regions and of RVFV L, M, and S segments [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Virus was isolated from all 4 RVFV-positive mosquito batches. Phylogenetic analysis of partial L-, S-, and M-segment sequences showed that the strains responsible for the outbreak of RVF re-emerged from a local RVFV focus, showing the need for continuous surveillance [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The RVFV-positive samples were partially sequenced and a phylogenetic analysis was conducted, which revealed a possible association between the observed cases in Mauritania and the RVFV isolates reported from Senegal in 2013. The RVFV disease outbreak in Mauritania reported 57 confirmed cases as well as 12 deaths [123].…”
Section: Mauritaniamentioning
confidence: 99%